Cultivating the marine microalga Nannochloropsis salina under various nitrogen sources: effect on biovolume yields, lipid content and composition, and invasive organisms - Campos, H.; Boeing, W. J.; Dungan, B. N.; Schaub, T.
Algae can be a viable source for biofuel production, but the source of nitrogen used to cultivate could affect algae yields. Here, we observe how various nitrogen treatments can impact the growth and biovolume of microalga Nannochloropsis salina as well as invasion of undesired organisms. Invading organisms increase the likelihood of crashes of the desired microalgae culture. Experiments were conducted over 28 days in open aquaria in a greenhouse. We used five different nitrogen treatments; ammonium chloride (NH4Cl), ammonium hydroxide (NH4OH), sodium nitrate (NaNO3), urea (CH4N2O), and a mixture of all these sources. Highest values for Maximum Sustainable Yield (MSY), a measure of potential harvest rate based on population productivity, were observed in the urea treatment, but cell size was smaller compared to other treatments. Sodium nitrate and the mixture of nitrogen sources also had high MSY values but larger cell sizes, making them the treatments with highest total biovolume. The highest percentages of lipid by weight, but also highest densities of invading organisms were observed in the mixed treatment. Our results suggest that tradeoffs between biovolume and lipid yields as well as culture success can ultimately decide what nitrogen sources to use.
Keywords: MICROALGAE BIODIESEL; NITROGEN MEDIA; BIOMASS PRODUCTION; LIPID ACCUMULATION; INVASIVE SPECIES; NANNOCHLOROPSIS